Answer:
Each hot dog = $3
Each french fry = $2
Step-by-step explanation:
First, lets define our variables:
x = Hotdog
y = fries
Next, you need to set up a cost equation for both Toby and Bernie:
8x + 5y = 34
2x + 6y = 18
Now, we need to isolate one of the variable:
2x + 6y = 18
2x = 18 - 6y
x = 9 - 3y
Next, we need to insert this equation back into the first equation (8x+5y = 34) to find the cost of y (fries):
8x +5y = 34
8 (9-3y) + 5y = 34
72 - 24y + 5y = 34
72 - 19y = 34
19y = 38
y or fries = $2
Finally, we need to find the cost of each hotdog by using the cost of fries ($2) in one of the formulas:
2x + 6y = 18
2x + 6(2) = 18
2x + 12 = 18
2x = 6
x or hotdog = $3
I hope this helps!
-TheBusinessMan
Answer:
$3.72
Step-by-step explanation:
7.75*2=15.5
15.5+0.78=16.28
20-16.28=3.72
(8xn)+6 would be your equation. please mark me as brainiest.
Answer:
D (or the last one) it has multiple faces upon one face do it doesn't count. it also isn't a triangle it's a pentagon.
Step-by-step explanation:
big brain time